PENERAPAN ECO ENZYME PADA PEMBELAJARAN SAINS TERKAIT LINGKUNGAN DI TAMAN KANAK-KANAK - srinandarahmawati srinandarahmawati; Yaswinda Yaswinda (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2021)
The following study aims to analyze the application of eco enzyme in environmental science learning in kindergartens. The method used in this research is literature study method. By collecting data using secondary data, it is achieved by analyzing various scientific articles, journals, books and literature references that are related to the problems and thoughts to be studied. Then when the data has been obtained, data analysis is carried out by connecting the existing problems with relevant concepts and theories. From various analysis results, with several references, it shows that the activity of eco enzyme can be applied in environmental science learning. With various environmental damage, one of which is caused by household waste that occurs natural disasters, for example floods. So it is important to have a sense of care, empathy and also have a critical mindset in protecting environmental damage that will occur from an early age, through learning science related to the environment which is learning that studies self-awareness of natural disasters that will arise due to human activity. To instill if you care and love the environment from early childhood, namely by carrying out eco enzyme activities in environmental science learning in Kindergarten. So it can be concluded that by carrying out eco enzyme activities in early childhood can foster caring souls, love for the environment, produce their own products, use their own products, have an entrepreneurial spirit from an early age, have the convenience of getting the materials and containers used. , has many benefits in everyday life, helps reduce household waste, has economic value and also has a high social spirit.